The kinocardiograph for assessment of fluid status in patients with acute decompensated heart failure - Cyrille Herkert; Ignace De Lathauwer; Mayke vanLeunen; Rudolph Ferdinand Spee; Paniz Balali; Pierre‐Francois Migeotte; Amin Hossein; Yuan Lu; Hareld Marijn Clemens Kemps (ESC Heart Failure, 2023)
Abstract Aims To improve telemonitoring strategies in heart failure patients, there is a need for novel non‐obtrusive sensors that monitor parameters closely related to intracardiac filling pressures. This proof‐of‐concept study aims to evaluate the responsiveness of cardiac kinetic energy (KE) measured with the Kinocardiograph (KCG), consisting of a seismocardiographic (SCG) sensor and a ballistocardiographic (BCG) sensor, during treatment of patients with acute decompensated heart failure. Methods and results Eleven patients with acute decompensated heart failure who were hospitalized for treatment with intravenous diuretics received daily KCG measurements. The KCG measurements were compared with the diameter of the inferior vena cava (IVC) and body weight. Follow‐up stopped at discharge, that is, in the recompensated state. Median (interquartile range) weight and IVC diameter decreased significantly after diuretic treatment [weight 74.5 (67.6–98.7) to 73.3 (66.7–95.6) kg, P = 0.003; IVC diameter 2.47 (2.33–2.99) to 1.78 (1.65–2.47) cm, P = 0.03]. In contrast with BCG measurements, significant changes in median KE measured with SCG were observed during the passive filling phase of the diastole [SGG: 0.48 (0.39–0.60) to 0.69 (0.56–0.84), P = 0.026; BCG: 0.68 (0.46–0.73) to 0.68 (0.59–0.82), P = 0.062], the active filling phase of the diastole [SCG: 0.38 (0.30–0.61) to 0.31 (0.09–0.47), P = 0.016; BCG: 0.29 (0.17–0.39) to 0.26 (0.20–0.34), P = 0.248], and the ratio between the passive and active filling phases [SCG: 2.76 (1.68–5.30) to 5.02 (3.13–10.17), P = 0.006; BCG: 5.87 (3.57–7.55) to 5.27 (3.95–9.43), P = 0.790]. The correlations between changes in KE during the passive and active filling phases, using SCG, and changes in weight or IVC were non‐significant. Systolic KE did not show significant changes. Conclusion KE measured with the KCG using SCG is highly responsive to changes in fluid status. Future research is needed to confirm its accuracy in a larger study population and specifically its application for detection of clinical deterioration in the home‐environment.